2018
DOI: 10.1007/s00417-018-3925-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy for optic disc pit maculopathy: a long-term follow-up study

Abstract: Vitrectomy with induction of PVD is a safe and successful therapeutic option for the treatment of optic disc pit maculopathy. The adjunct of ocriplasmin might facilitate the induction of PVD and reduce the risk of iatrogenic retinal holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
2
20
1
Order By: Relevance
“…Also, of the patients with attached macula, 80% required more than 180 days for reattachment to occur. This is in keeping with previous studies that showed that improvement of vision is related to restoration of the normal retinal morphology [10-14, 19, 21, 22, 25-31]. This becomes progressively more evident 6–12 months postoperatively, as submacular fluid is slow to resolve (Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, of the patients with attached macula, 80% required more than 180 days for reattachment to occur. This is in keeping with previous studies that showed that improvement of vision is related to restoration of the normal retinal morphology [10-14, 19, 21, 22, 25-31]. This becomes progressively more evident 6–12 months postoperatively, as submacular fluid is slow to resolve (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Improvement of vision was achieved in 89% of our cases, with a mean visual gain of almost 3 lines on the Snellen chart at the end of the follow-up time, and 67% had a final BCVA of 0.5 or better. This compares favourably with other functional results [10-14, 19, 22, 25-31]. Similar functional outcomes have been reported by D’Souza et al [16] and Nawrocki et al [17] using the same surgical procedure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This report uniquely demonstrates a very large maculoschisis cavity in the outer retina with a prominent PMC. In contrast to many other ODP reports that show shallow schisis channels overlying relatively large macular detachments,11,14 here a “giant” schisis cavity developed and apparently remained a pure maculoschisis until finally breaking through a microscopic outer layer hole to form a small detachment at the fovea (Figure 1C), as first described by Lincoff et al4…”
Section: Discussioncontrasting
confidence: 62%
“…Relatively few investigations have evaluated surgical and visual outcomes from a long-term perspective (Avci et al 2013;Ooto et al 2014;Rayat et al 2015;Abouammoh et al 2016;Bottoni et al 2018;Bloch et al 2019). In the present study, we aimed to investigate the results of patients who operated at the € Orebro University Hospital for ODP, with the purpose of assessing long-term surgical results, anatomical healing, as well as present visual function and symptoms (Table 1).…”
Section: Introductionmentioning
confidence: 99%